Pengaruh Status Sosial Ekonomi Terhadap Prestasi Belajar Peserta Didik Sd Negeri 10 Tikep - La Ubi (Prodi PGSD Unsultra, 2020)
This study aimed to analyze the effect of socio-economic status on student achievement at Elementary School 10 Tikep. The sample of this study consisted of 238 students. This research used a survey method. Socio-economic status data were collected using a questionnaire, while learning achievement data were obtained from the results of mid-semester and end-semester tests. The results of the inferential analysis showed that the significance value (sig.) = 0.000 < 0.05, which means that socio-economic status has a positive effect on students’ learning achievement at Elementary School 10 Tikep.